Anthropogenic landforms in an urbanized alluvial-coastal plain (Rapallo city, Italy) - Pierluigi Brandolini (Taylor & Francis Group, 2021)
This paper describes the anthropogenic landforms of the alluvial-coastal plain of Rapallo (Eastern Liguria, NW Italy). Since the second half of the nineteenth-century Rapallo experienced a progressive urban sprawl that became particularly intense after the Second World War and severely modified the former landforms. The identification and mapping of morphological changes was performed through a multi-temporal comparison of historical and recent maps and aerial photographs, an analysis of geo-thematic maps and urban planning documents, an interpretation of stratigraphic data from boreholes, and a field survey activity. The main anthropogenic interventions that shaped the urban landscape of Rapallo were riverbed diversions and channelization, excavations, fillings, and embankments construction along the shoreline. These elements highlight the relevant extent of the human imprint on the pristine environment. Furthermore, the identified anthropogenic geomorphological features, combined with the local physiographic and climatic features, increased flood and sea storm hazards and risks.